The Quality Evaluation of Postharvest Strawberries Stored in Nano-Ag Packages at Refrigeration Temperature - Zhang, Cheng (Polymers (Basel), 2018)
Different percentages (0%, 1%, 5%, and 10%) of nano-Ag particles were added to polylactic acid (PLA) to make an active nanocomposite packaging film. Strawberries were packaged by the nanocomposite films and stored at 4 ± 1 °C for 10 days. The freshness of strawberries was assessed by regularly measuring the physicochemical properties of the strawberries in each packaging film. The difference in the freshness of strawberries was evaluated by determining the following parameter changes: weight loss, hardness, soluble solids, titratable acid, color, vitamin C, total phenol, free radical scavenging activity, peroxidase activity, and sensory evaluation. The results revealed that the active nanocomposite packaging film has better preservation effect when compared with pure PLA film. Its preservation effect is mainly reflected in the more effective reduction of vitamin C loss, delaying the decline of total phenols and 1-Diphenyl-2-picrylhydrazyl (DPPH) in strawberries. It also showed better physical properties. The results showed that the PLA nanocomposite packaging film could effectively preserve freshness of strawberries.